Extralobar lung sequestration associated with fatal neonatal respiratory distress - Bliek, A. J. (1971)
The radiological and pathological findings of lung sequestration in a premature infant are described. There was a left-sided variant of the extralobar type with double systemic arterial blood supply, single systemic venous drainage, and an incomplete bronchial tree for the remainder of the left lung.